Characteristics and mechanisms of sea (salt) water intrusion in Laizhou City, Shandong Province, China - Kong, Linghao; Chu, Hongxian; Hou, Guohua; Zeng, Jiao; Zhao, Liyuan; Han, Xiangcai; Li, Yachao; Zhou, Faqiao; Yin, Meiling; Zhang, Xuzhen (Frontiers in Marine Science, 2025)
Sea (salt) water intrusion is a significant and ongoing geological disaster, and in recent years, it has become a notable concern for Laizhou City, Shandong Province. To identify the characteristics and mechanism of sea (salt) water intrusion in Laizhou City, samples of different types of water bodies (such as seawater, freshwater, slightly brackish water, brackish water, saline water, and brine) were systematically collected from the coastal zone area. The hydrochemical composition and evolution characteristics of the water bodies and the current situation, trends, and causes of sea (salt) water intrusion were analyzed. In 2020, the sea (salt) water intrusion reached 645.76 km2 (including 151.64 km2 of serious intrusion area), which is the largest ever recorded. The sea (salt) water intrusion had a strip-sheet distribution. From land to sea, groundwater gradually transitioned from the HCO3·SO4·Cl-Ca type to SO4·Cl-Na·Ca and SO4·Cl-Na types and then evolved to the Cl-Na type. Furthermore, from land to sea, the dominant cations and anions shifted from Ca2+ and HCO3- to Na+ and Cl-. The influence of seawater or brine gradually increased, that of Ca2+ and HCO3- gradually decreased; whereas that of Cl- and Na+ gradually increased, showing a division zone of freshwater → slightly brackish water → brackish water → saline water → seawater (brine) in the macroscopic territory. The freshwater, slightly brackish water, and brackish water bodies in the study area were controlled by evaporation and concentration processes and rock weathering leaching, whereas the saline water and brine were primarily controlled by evaporation and concentration processes. Groundwater salinity in the study area mainly originates from sea (salt) water intrusion, and locally groundwater salinity mainly originates from mineral dissolution or human activities. In addition, significant cation exchange adsorption occurred in slightly brackish and brackish water. Overall, these results will help to prevent and control seawater intrusions and improve disaster management.